Moving to continuous facial expression space using the MPEG-4 facial definition parameter (FDP) set - Tsapatsoulis, Nicolas; Karpouzis, Kostas; Kollias, Stefanos D. (My University, 2000)
Research in facial expression has concluded that at least six emotions, conveyed by human faces, are universally associated with distinct expressions. Sadness, anger, joy, fear, disgust and surprise are categories of expressions that are recognizable across cultures. In this work we form a relation between the description of the universal expressions and the MPEG-4 Facial Definition Parameter Set (FDP). We also investigate the relation between the movement of basic FDPs and the parameters that describe emotion-related words according to some classical psychological studies. In particular Whissel suggested that emotions are points in a space, which seem to occupy two dimensions: activation and evaluation. We show that some of the MPEG-4 Facial Animation Parameters (FAPs), approximated by the motion of the corresponding FDPs, can be combined by means of a fuzzy rule system to estimate the activation parameter. In this way variations of the six archetypal emotions can be achieved. Moreover, Plutchik concluded that emotion terms are unevenly distributed through the space defined by dimensions like Whissel's; instead they tend to form an approximately circular pattern, called 'emotion wheel,' modeled using an angular measure. The 'emotion wheel' can be defined as a reference for creating intermediate expressions from the universal ones, by interpolating the movement of dominant FDP points between neighboring basic expressions. By exploiting the relation between the movement of the basic FDP point and the activation and angular parameters we can model more emotions than the primary ones and achieve efficient recognition in video sequences
Keywords: Facial expression; Fuzzy sets; Mathematical models